Organisational learning and the organisational life cycle: The differential aspects of an integrated relationship in SMEs. Issue 1 (4th January 2016) - Tam, Steven; Gray, David E
Abstract : Purpose: – The purpose of this study is to relate the practice of organisational learning in small- and medium-sized enterprises (SMEs) to the organisational life cycle (OLC), contextualising the differential aspects of an integrated relationship between them. Design/methodology/approach: – It is a mixed-method study with two consecutive phases. In Phase I, 30 Hong Kong SMEs identified through theoretical sampling were classified into three life-cycle stages – inception, high growth and maturity. In Phase II, their employees' learning practices (grouped by learning levels) were statistically compared using the analysis of variance and then followed up for confirmation with qualitative semi-structured interviews. Findings: – This study uniquely suggests the nature of a relationship between SME organisational learning and the OLC. Empirical results show that three of the four learning levels (individual, group, organisational and inter-organisational) practised in SMEs are varied in importance between life-cycle stages. Research limitations/implications: – Comparative studies are encouraged in other parts of the world to strengthen the findings – with either SMEs or large organisations. Practical implications: – The study informs SME owner/managers about what is important for employee learning at different business stages so that appropriate learning strategies or human resource development policies can be formulated in a timely fashion to promote competitiveness. Originality/value: – It is among the first studies to connect SME learning with organisational growth. The relationships found serve as a sound foundation for further empirical investigations.